A Hierarchically Structured Graphene/Ag Nanowires Paper as Thermal Interface Material - Le Lv; Junfeng Ying; Lu Chen; Peidi Tao; Liwen Sun; Ke Yang; Li Fu; Jinhong Yu; Qingwei Yan; Wen Dai; Nan Jiang; Cheng-Te Lin (Nanomaterials, 2023)
With the increase in heat power density in modern integrating electronics, thermal interface materials (TIM) that can efficiently fill the gaps between the heat source and heat sinks and enhance heat dissipation are urgently needed owing to their high thermal conductivity and excellent mechanical durability. Among all the emerged TIMs, graphene-based TIMs have attracted increasing attention because of the ultrahigh intrinsic thermal conductivity of graphene nanosheets. Despite extensive efforts, developing high-performance graphene-based papers with high through-plane thermal conductivity remains challenging despite their high in-plane thermal conductivity. In this study, a novel strategy for enhancing the through-plane thermal conductivity of graphene papers by in situ depositing AgNWs on graphene sheets (IGAP) was proposed, which could boost the through-plane thermal conductivity of the graphene paper up to 7.48 W m−1 K−1 under packaging conditions. In the TIM performance test under actual and simulated operating conditions, our IGAP exhibits strongly enhanced heat dissipation performance compared to the commercial thermal pads. We envision that our IGAP as a TIM has great potential for boosting the development of next-generation integrating circuit electronics.